Global carbon emission governance and green trade: the moderating role of political stability and trade diversity - Guo, Mengyao; Cui, Yiniu; Li, Zizhuo; Wang, Jingjing; Qiao, Shuo (Frontiers in Environmental Science, 2025)
In contrast to traditional trade, green trade fully considers the social costs of production, investment, and export following economic activities, building upon environmental governance and protection. While the promotion of green trade is a historical inevitability, countries must actively foster collaboration in new trade initiatives to meet carbon reduction targets. However, during the process of encouraging the expansion of green trade, there is a risk that countries may further increase their carbon emissions, thereby exacerbating environmental degradation. This study utilizes panel data from G20 countries between 2000 and 2022 to examine the relationship between carbon emissions and green trade through an Ordinary Least Squares regression model, with the primary objective of determining whether green trade increases or decreases carbon emissions. To further explore the moderating role of trade diversity and political stability on the relationship between carbon emissions and green trade, a moderating effect regression model is also employed. Additionally, this paper introduces a quantile regression model to assess the varying impact of green trade on carbon emissions across different quantiles. The study’s findings indicate that green trade tends to result in higher carbon emissions. Under conditions of political stability, the potential for green trade to reduce carbon emissions diminishes. Conversely, the positive impact of trade diversification inhibits the positive effects of green trade on carbon emissions. The coefficient of green trade is positive and steadily increases across various quantiles of carbon emissions. At the 0.9 quantile, the association is significantly positive, offering further evidence that green trade could lead to increased carbon emissions. Based on these findings, the paper suggests that a significant reduction in carbon emissions may not be achievable in the near future, and that the path to expanding green trade is both challenging and protracted. Therefore, governments worldwide must carefully implement green trade practices, protect the environment, achieve sustainable economic growth, and promote the rational allocation of resources as prerequisites for the long-term development of the green sector.